Strategi Komunikasi Digital DPR RI dalam Membangun dan Mempertahankan Citra Kredibel di Kalangan Pelajar Melalui Akun Instagram @Parlemen_Remaja - Shavira Helena Rahayu Keesya Obyga; Puri Bestari Mardani (Jayapangus Press, 2026)
Digital communication strategies have become crucial for public institutions amid growing social pressures in both public and digital spaces. The dynamics of protest issues directed toward DPR RI on social media reflect social pressure associated with a significant decline in public trust, particularly among students. Students are considered a pre-political group undergoing the formation of social awareness and critical attitudes, making them vulnerable to political opinions and issues circulating on social media. This study aims to analyze the digital communication strategy of DPR RI through the Instagram account @Parlemen_Remaja as part of building and maintaining a credible institutional image among students. This research employed a qualitative case study approach using in-depth interviews, Instagram account observation, documentation, and literature study. Data were analyzed using the Miles and Huberman model with the assistance of Nvivo 12 software. The study was based on the concepts of digital communication strategy, the Segmentation, Targeting, and Positioning (STP) model, and credibility. The findings indicate that DPR RI’s digital communication strategy was implemented through student segmentation as the target audience, visually engaging content, and the positioning of a credible institutional image through trustworthy, accurate, neutral, and comprehensive information. However, the communication strategy has not been fully optimized, as it still demonstrates limited dialogic space regarding public issues. This study offers a new perspective that digital communication strategies based on the STP model and credibility play an important role in public institutions while also revealing tensions between institutional neutrality and the demand for public responsiveness in digital spaces.